PENGARUH LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT ASTRA OTOPARTS TBK DIVISI SSC (Shared Service Centre) - Dian Anggraeni; Eddy Sanusi Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The research objective was to determine the effect of work environment and career development on employee performance of PT. Astra Otoparts Tbk Division SSC (Shared Service Center). The research method, in this study using primary and secondary data sources, where the data collection is done by field research and library research. Respondents in this study were all employees of PT. Astra Otoparts Tbk Division SSC (Shared Service Center) as many as 72 respondents using the slovin technique with a tolerance level of 5 percent. The data collection technique used a questionnaire and the sampling technique used random sampling. The results of the study have an effect both partially and simultaneously on work environment and career development on employee performance at PT. Astra Otoparts Tbk Division SSC (Shared Service Center).